A descriptive analysis of the English syntactic structures used by Quirino High School students in their themes - Parayno, Perlita Lacambra 1944-
The English syntactic structures used by Quirino High School students in their themes are analyzed linguistically and mathematically to determine the syntactic structures that are generally used and to identify syntactic structures that are used to lengthen simple sentences. Findings of the study may guide English teachers in interpreting students' ability to use a variety of syntactic structures.